2013
DOI: 10.1021/am302676a
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient TiO2–xCx Nano-heterojunction Photocatalyst for Visible Light Induced Antibacterial Applications

Abstract: Visible-light-induced antibacterial activity of carbon-doped anatase-brookite titania nano-heterojunction photocatalysts are reported for the first time. These heterostructures were prepared using a novel low temperature (100 °C) non-hydrothermal low power microwave (300 W) assisted method. Formation of interband C 2p states was found to be responsible for the band gap narrowing of the carbon doped heterojunctions. The most active photocatalyst obtained after 60 minutes of microwave irradiation respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 246 publications
(123 citation statements)
references
References 52 publications
2
120
0
1
Order By: Relevance
“…The Si and F modified coatings reduced the bacterial adhesion by 68% at 12 h compared with stainless steel [46]. A number of doped/co-doped photocatalytic materials were also reported [42,[47][48][49][50][51][52][53][54] to show antibacterial action. However, a direct comparison of the efficiency of these catalysts is not possible due to the lack of a standard testing protocol.…”
Section: Resultsmentioning
confidence: 97%
“…The Si and F modified coatings reduced the bacterial adhesion by 68% at 12 h compared with stainless steel [46]. A number of doped/co-doped photocatalytic materials were also reported [42,[47][48][49][50][51][52][53][54] to show antibacterial action. However, a direct comparison of the efficiency of these catalysts is not possible due to the lack of a standard testing protocol.…”
Section: Resultsmentioning
confidence: 97%
“…It was also suggested that despite the decrease in band gap energy, metals were not always successfully introduced into the TiO 2 framework, and that the remaining metals on the outside surface sheltered the photoreaction sites [44]. Significant attention has been directed at reducing the band gap and in turn increasing the visible light activity of TiO 2 by doping with a range of non-metal elements including nitrogen [34,[45][46][47][48][49], carbon [43,[50][51][52][53], sulphur [54][55][56], phosphorous [57], boron [58,59], oxygen [60], and fluorine [61,62], along with heterojunctions [63][64][65][66][67] and combinations of these elements [68][69][70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 composites with added bactericide metal/oxides deposited by colloids calcined on heat resistant surfaces has been the subject of many recent studies [1,2]. The effect of TiO 2 -N,S nanoparticles and sputtered TiO 2 films to increase visible light absorption and accelerate bacterial inactivation kinetics have been recently reviewed by Dionysiou et al, [3,4], Foster et al, [5], Pillai et al, [6][7][8], Byrne et al, [9], Navabpour et al, [10], Verran et al, [11] and Bahnemann et al, [12,13]. Since the uniform and reproducible adhesion of TiO 2 films on substrates starting form colloidal depositions has been shown to present serious problems, antibacterial TiO 2 and TiO 2 -composites have been recently prepared by chemical vapor deposition (CVD), by RF-sputtering and evaluated in regards to their bactericide features [14][15][16].…”
Section: Introductionmentioning
confidence: 99%